Performance of Tomicus yunnanensis and Tomicus minor (Col., Scolytinae) on Pinus yunnanensis and Pinus armandii in Yunnan, Southwestern China - Tao Zhao; Bo Långström (Psyche: A Journal of Entomology)
Pine shoot beetles, Tomicus yunnanensis Kirkendall and Faccoli and Tomicus minor Hartig (Col., Scolytinae), have been causing substantial mortality to Yunnan pine (Pinus yunnanensis Franch) in Yunnan, southwestern China, whereas only a few Armand pine (Pinus armandii Franch) were attacked by the beetles. In order to evaluate the suitability of P. armandii as host material for the two Tomicus, adults of both Tomicus were caged on living branches and felled logs of the two pines during shoot feeding and trunk attack phase, respectively. More beetles survived on the living branches of P. yunnanensis than on P. armandii. Tomicus yunnanensis and T. minor produced similar progeny in the logs of the two pines. The sex ratio and developmental period were not affected by host species, but the brood beetles emerging from Armand pine weighed less than those from Yunnan pine, suggesting that P. armandii are less suitable to be host of T. yunnanensis and T. minor.